2021
DOI: 10.3390/en14206495
|View full text |Cite
|
Sign up to set email alerts
|

GHGs Emission from the Agricultural Sector within EU-28: A Multivariate Analysis Approach

Abstract: Climate mitigation and adaptation planning (CMAP) has recently been implemented across the EU-28 to reduce GHG emissions (CO2, CH4, N2O). Thus, the aim of this study was to provide an overview of GHG emissions from the agricultural sector in the EU-28 from 1990 to 2019, and cluster the EU-28 countries regarding their total GHG emissions. The results emphasize the positive impact of CMAP through a negative trend of the total GHG emissions (−2653.01 thousand tons/year, p < 0.05). Despite the positive and not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 44 publications
0
4
0
1
Order By: Relevance
“…As a result, a comprehensive approach is necessary to address these complexities. In addition, IoT and AI can help reduce the effects of climate change and greenhouse gas emissions, further emphasizing the significance of these technologies in modern agriculture [57][58][59][60]. The research studies' comparisons illustrate multiple approaches for soil and plant sensing systems in precision agriculture, each with unique benefits and limitations.…”
Section: Ai Real-time Monitoring and Big Data (Mining And Analyzing)mentioning
confidence: 99%
“…As a result, a comprehensive approach is necessary to address these complexities. In addition, IoT and AI can help reduce the effects of climate change and greenhouse gas emissions, further emphasizing the significance of these technologies in modern agriculture [57][58][59][60]. The research studies' comparisons illustrate multiple approaches for soil and plant sensing systems in precision agriculture, each with unique benefits and limitations.…”
Section: Ai Real-time Monitoring and Big Data (Mining And Analyzing)mentioning
confidence: 99%
“…The study reasoned that there are detrimental impacts on environmental regulation’s strictness due to global uncertainty and corruption. Corruption and political uncertainty are mutually dependent (Fredriksson & Svensson, 2003; Harsányi et al, 2021). Additionally, Saud et al (2019) also reported similar consequences of corruption-environmental quality, corruption-environmental regulations for 1998 to 2012 in China.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Sustainable agriculture is the most diverse area where IoT can be used, as the characteristics of biodiversity, stochastic phenomena (weather), the symbiosis of living and inanimate systems require a complex approach (Division et al;Wang et al, 2019;Bhatta and Thangadurai, 2019). IoT/AI can also play a significant role in mitigating adverse climate change and GHG (Greenhouse Gas) emissions (Abd El-Mawla et al, 2019;Harsányi et al, 2021). One of the great advantages of IoT in agriculture is that it is possible to prepare for events that come from further distances from a given area (e.g., insect pest invasion) by using the data of the IoT station installed there.…”
Section: Iot and Smart Agriculturementioning
confidence: 99%